Pain is a family matter: Quality of life in mothers and fathers of youth with chronic pain. (3rd April 2019) - Benjamin, Julia Z.; Harbeck‐Weber, Cynthia; Sim, Leslie
Abstract: Background: Most research on family impacts of paediatric chronic pain has been conducted with mothers, and therefore, little is known about fathers' adjustment. However, it is well established that caring for a child with chronic pain takes a toll on caregiver well‐being. Parents of children with chronic pain have been found to experience high levels of anxiety, depression, and parenting stress. As such, the goal of this study was to examine differences between mothers and fathers of youth with chronic pain, explore interaction effects between parent gender and child variables, and compare parents' scores to national norms. Methods: Participants included 160 matched mothers and fathers of youth with chronic pain participating in an interdisciplinary pain rehabilitation programme. At admission, parents completed the Center for Epidemiological Studies–Depression scale and SF‐36 to assess depression and health‐related quality of life. T tests and analysis of variance were used to explore differences between mothers and fathers and population norms. Results: Mothers reported experiencing significantly poorer functioning than did fathers in the domains of emotional role interference, social functioning, and vitality. Differences remained significant when controlling for other psychosocial variables using multiple regression. Child gender and depression level were found to be significant predictors of parent mental health, with mothers' mental health more negatively influenced by child depression. Additionally, mothers' scores in mental health domains were significantly lower than population norms. Conclusions: These findings highlight the importance of identifying the ways in which chronic pain in youth may affect parents differently in order to enhance caregiver support and interventions.